2008
DOI: 10.1002/anie.200800857
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Loaded Superparamagnetic Iron Oxide Nanoparticles for Combined Cancer Imaging and Therapy In Vivo

Abstract: Multitasking rust ball: The questions of where a tumor is located, whether drugs are properly delivered to the tumor, and what the therapeutic response of the tumor is, could be answered by using simple but smart, drug‐loaded superparamagnetic iron oxide nanoparticles that can accumulate in tumor with high efficiency thanks to the presence of rationally engineered polymer coating layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
293
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 566 publications
(294 citation statements)
references
References 40 publications
0
293
0
1
Order By: Relevance
“…Following their results, accumulation of SPIONs in gliosarcomas can be significantly enhanced by magnetic targeting and successfully quantified by MR imaging with no toxicity observation. Yu et al 137 reported that the excellent passive tumor targeting efficiency of thermally cross-linked (TCL)-SPIONs allowed detection of tumors by MR imaging and at the same time delivery of sufficient amounts of anticancer drugs that in turn were released from the nanoparticles to exhibit anticancer activity. Consequently, doxorubicin@TCL-SPIONs showed exceptional antitumor effects without any systemic toxicity.…”
Section: In Vivo Toxicity Of Spionsmentioning
confidence: 99%
“…Following their results, accumulation of SPIONs in gliosarcomas can be significantly enhanced by magnetic targeting and successfully quantified by MR imaging with no toxicity observation. Yu et al 137 reported that the excellent passive tumor targeting efficiency of thermally cross-linked (TCL)-SPIONs allowed detection of tumors by MR imaging and at the same time delivery of sufficient amounts of anticancer drugs that in turn were released from the nanoparticles to exhibit anticancer activity. Consequently, doxorubicin@TCL-SPIONs showed exceptional antitumor effects without any systemic toxicity.…”
Section: In Vivo Toxicity Of Spionsmentioning
confidence: 99%
“…Envisaging new methods for the synthesis of monodisperse magnetic nanoparticles (NPs) constitutes one of the most active and challenging research fields in materials science due to the almost infinite uses foreseen for these systems in biomedicine, 1 magnetic recording, 2 energy production, etc. 3 Many of these applications rely on the possibility of obtaining well dispersed assemblies of NPs in a non-magnetic matrix (normally diamagnetic solids like polymers, SiO 2 , etc).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles of iron oxide possess superparamagnetic properties, whereby magnetism is 69 only present when under direct energy from an external magnetic field [9]. Other advantages of iron 70 oxide include its ability to be used in magnetic resonance imaging and induce cytotoxicity through near 71 infrared induced hyperthermia [10]. Unfortunately, iron oxide alone in physiological media is unstable, 72 resulting in oxidation, aggregation and precipitation [10][11][12][13].…”
mentioning
confidence: 99%